Plant cell wall degrading and remodeling proteins: current perspectives - Rosa E Quiroz-Castañeda; Jorge L Folch-Mallol (Biotecnología Aplicada, 2011)
Lignocellulose constitutes a raw material with considerable potential for the production of fermentable sugars and the generation of biofuels. In nature, lignocellulosic waste from forestry, agriculture and gardening acts as the preferred carbon source of a number of bacteria and fungi endowed with the required ligninolytic machinery. These hydrolytic activities could potentially be complemented with those from other proteins that remodel the structure of cell walls, such as expansins, a group of proteins originally identified in plants that have the capacity of relaxing cell wall tension to allow cell growth. Expansins participate in processes where remodeling of the plant cell wall is required: organogenesis, fruit ripening, and growth of the pollen tube, among others. Expansins and expansin-like proteins have been proposed to act by disrupting the hydrogen bonds binding together cellulose fibrils and cellulose and other polysaccharides through a non-enzymatic process, enhancing subsequent degradation. In this manuscript, a review on plant cell wall composition and ligninolytic enzymes from cell wall-degrading bacteria and fungi is presented. Proteins with expansin-like activity, their properties and their potential application to enhance sugar release from lignocellulosic material are also reviewed.